The Students’ Learning Interest in Quadratic Function Topics Using Geogebra - Melissa, Margaretha Madha; Redianto, Alberto; Wiwahanama, Antonius Venta; Maturbongs, Lily Maria (Edumatika, 2023)
The impact of students' learning interest on their academic achievement is widely acknowledged; however, a significant number of students still exhibit low levels of interest. Employing effective learning media has been identified as a strategy to enhance learning interest, with dynamic tools such as Geogebra being recognized for their potential. This study aimed to describe students' learning interest by utilizing Geogebra in the context of the quadratic function topic. The research employed qualitative methods and a descriptive approach, involving four students as respondents from a private Senior High School in Yogyakarta, Indonesia. The instructional intervention consisted of mathematics lessons on quadratic functions using Geogebra. Data collection utilized unstructured interviews and close-ended questionnaires, incorporating 22 questions across five indicators of students' learning interest. The questionnaire results revealed an average percentage of students' learning interest falling within the strong category across all indicators. The findings suggest a strong preference among respondents for learning utilizing Geogebra, primarily attributed to its visually appealing interface. Consequently, students exhibited a high level of interest in studying the quadratic functions topic when facilitated by Geogebra.